Joseph the Just and Matthew’s Matrix of Mercy: The Redefinition of Righteousness - Jonathan Pennington (Journal of Moral Theology, 2021)
One of the first characters to appear in the New Testament and the first person to be called "righteous" is Joseph, the husband of Mary. Though he speaks no words and only appears in the earliest stories (Matt 1:18-25; 2:13-23), Joseph becomes a key exemplar of virtue for the Gospel of Matthew. Matthew employs Joseph as a righteous man as an exemplar of Jesus's redefinition of "righteousness" as mercy. Contrary to many contemporary Jewish assumptions, in Matthew Jesus emphasizes that right action before God is largely defined as showing mercy toward others.